2003
DOI: 10.1128/iai.71.10.5662-5669.2003
|View full text |Cite
|
Sign up to set email alerts
|

Oral Immunization of BALB/c Mice with Giardia duodenalis Recombinant Cyst Wall Protein Inhibits Shedding of Cysts

Abstract: The process of encystation is a key step in the Giardia duodenalis life cycle that allows this intestinal protozoan to survive between hosts during person-to-person, animal-to-person, waterborne, or food-borne transmission. The release of cysts from infected persons and animals is the main contributing factor to contamination of the environment. Genes coding for cyst wall proteins (CWPs), which could be used for developing a transmission-blocking vaccine, have been cloned. Since the immunogenicity of recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 26 publications
3
37
0
1
Order By: Relevance
“…Our observed reduction level compares quite well with the 75 % reduction level demonstrated from a previous study where mice were orally immunized with the full-length 39 kDa form of recombinant CWP2 produced by E. coli (Larocque et al, 2003). Since both stages of the Giardia life cycle occur simultaneously in the intestine (Campbell & Faubert, 1994b), the immune clearance of the cysts from the intestinal lumen may be due to antibodies directed at the trophozoite stage.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our observed reduction level compares quite well with the 75 % reduction level demonstrated from a previous study where mice were orally immunized with the full-length 39 kDa form of recombinant CWP2 produced by E. coli (Larocque et al, 2003). Since both stages of the Giardia life cycle occur simultaneously in the intestine (Campbell & Faubert, 1994b), the immune clearance of the cysts from the intestinal lumen may be due to antibodies directed at the trophozoite stage.…”
Section: Discussionsupporting
confidence: 89%
“…The intestinal mucosal immune system of mice infected with Giardia muris recognizes CWP2 as a foreign antigen since specific antibodies are produced locally (Larocque et al, 2003). In addition, we have reported that immunization of BALB/c mice with the 39 kDa form of CWP2 reduces cyst shedding in the murine model of giardiasis when it is delivered orally with cholera toxin (Larocque et al, 2003). CWP2 has two forms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Giardia ' cyst wall is biologically important as a simple model extracellular matrix, with both structural and signal transduction functions [21], [22]. Encystation contributes to immune evasion [23] by two distinct pathways: first, the cyst wall covers the trophozoite surface during encystation and sequesters it from host defenses and second, encystation leads to switching of VSPs [18], [24], [25]. Despite its importance, the composition, architecture, and formation of the cyst wall are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Both LAB were engineered to express recombinant G. lamblia cyst wall protein 2 (CWP2) on the bacterial cell surface as a fusion to the C terminal half of the M6 molecule. CWP2 was previously shown to reduce cyst excretion in infected animals following mucosal immunization with cholera toxin as an adjuvant (Larocque et al 2003). Interruption of encystations is an attractive control measure against Giardia transmission, as the cysts allow parasite survival in the environment and thus transmission between susceptible hosts.…”
Section: Factors Influencing the Immunogenicity Of Lab Vaccinesmentioning
confidence: 99%